Mercury content in the gallstones and bile of Thai people (Chiang Mai and Bangkok) and Japanese - Srisukho S. (2014)
Mercury contents in the gallstones and bile of patients living in Thailand (Chiang Mai and Bangkok) and Japan were studied by neutron activation analysis. The correlation between contents in the gallstones and bile, and the amount of mercury in the diet and environment was investigated by comparing the contents in patients living in three different areas. The content in the bile of the Japanese patients was significantly greater than that of the Thai patients. The distribution of mercury contents in the pigment and rare stones of patients living in Bangkok indicated a bipolarity. However, the distribution of the contents in cholesterol, pigment, and rare stones of Japanese patients did not indicate a bipolarity. Bipolarity would indicate the amount of mercury in dietary foods, and the pollution level of mercury. The mercury contents in the gallstones and bile would reflect the amount of mercury in the diet and environment.